Group hunting forays of wintering Northern Harriers, Circus cyaneus: An adaption of juveniles? - Bosakowski, T.; Smith, D.G. (Canadian Field-Naturalist, 1996)
The social interactions of a wintering population of Northern Harriers (Circus cyaneus) were studied in the Hackensack Meadowlands tidal marshes in New Jersey. Juvenile harriers were numerically dominant in the population and participated in hunting groups significantly more often than adult males or females. Group sizes varied from 2-4 birds (total groups observed = 66 duets, five trios and two quartets). The occasional inclusion of adults in a foraging group was usually the result of juveniles following the adult, presumably for the parasitic benefits of grabbing flushed prey or exploiting high yield foraging patches. Our observations suggested a non-territorial wintering harrier population documented by observations of 3-6 different individuals frequently hunting the same 12-ha area each day as well as random use of our study quadrats (3-ha) by individuals of all sexes and ages. Territorial defense was observed in only one adult female, which infrequently attempted to defend a territory. Overall, the prevalence of group-foraging behavior is consistent with the general lack of winter territory in this population.
Keywords: Circus cyaneus; Hackensack Meadowlands; New Jersey; Northern Harrier; dept.bio; following; foraging; group hunting; winter ecology; ⛔ No DOI found